Strategi Kebijakan Persatuan Bulutangkis Seluruh Indonesia dalam Mempersiapkan Atlet Pekan Olahraga Nasional 2021 di Papua - Widad, Zhinatul (Indonesian Journal of Political Studies, 2023)
The National Sports Fair (PON) is the Indonesian Games, which basically has an aim to improve the expectations of Indonesian athletes. This national sports weekend was organized for the purpose of maintaining unity and unity of the nation, housing potentially athlete seeds in appropriate sports charts 17,2017. The Central Government has a responsibility to organize the pounds and is carried out by the youth and sports ministry (Kenya) who assign to the Indonesian National Sports Committee (KONI) as its organizer. In Indonesia, badminton sports are quite popular in many communities, where badminton is often played by people’s sports because they are often played by people from urban or rural communities and played by adults, children, boys and girls. Althought badminton is not as popular as football, badminton sports have enough charm to attract Indonesian attendees to play badminton. Some Indonesians who like badminton sports are at the same time as whether they spend hours in front of television or in the stands. The study is a study using a descriptive qualitative study method that reviewed through interviews and observations with public-policy implementation theories.